1974
DOI: 10.1126/science.183.4122.306
|View full text |Cite
|
Sign up to set email alerts
|

Protons and Electrons in Jupiter's Magnetic Field: Results from the University of Chicago Experiment on Pioneer 10

Abstract: Fluxes of high energy electrons and protons are found to be highly concentrated near the magnetic equatorial plane from distances of ~ 30 to ~ 100 Jovian radii (R(J)). The 10-hour period of planetary rotation is observed as an intensity variation, which indicates that the equatorial zone of high particle fluxes is inclined with respect to the rotation axis of the planet. At radial distances [unknown] 20 R(J) the synchrotron-radiation-producing electrons with energies greater, similar 3 million electron volts r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…However, on the outbound trajectory both of our lower energy proton fluxes show slight maxima at the time of the second peak reported by Simpson et al (1974).…”
Section: Harmonic Analysis Of Proton Angular Distributionsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, on the outbound trajectory both of our lower energy proton fluxes show slight maxima at the time of the second peak reported by Simpson et al (1974).…”
Section: Harmonic Analysis Of Proton Angular Distributionsmentioning
confidence: 83%
“…Simpson et al (1974), have pointed out a small latitude effect for the > 35 MeV protons. Those protons showed very strong maxima near L -3.6 Rj.…”
Section: Harmonic Analysis Of Proton Angular Distributionsmentioning
confidence: 99%
“…[2] Pioneer 10 observations made over 30 years ago revealed that Jupiter is a source of high energy electrons in the heliosphere [Simpson, 1974]. High energy electron data from Pioneer 10 showed a monotonic increase in the electron flux from 1 AU as the spacecraft approached Jupiter (at 5.2 AU) and a gradual decrease as the spacecraft receded from Jupiter [Pyle and Simpson, 1977].…”
Section: Introductionmentioning
confidence: 99%
“…In 1973, when Pioneer 10 was approaching Jupiter, unexpected relativistic electron increases were detected in interplanetary space (Chenette et al, 1974;Simpson et al, 1974;Teegarden et al, 1974). The intensity of electron fluxes increased as Pioneer 10 approached Jupiter, showing that the relativistic electrons accelerated in the Jovian magnetosphere were released into the interplanetary medium.…”
Section: Introductionmentioning
confidence: 92%